Risk of cancer in individuals with alcohol and drug use disorders: a registry-based study in Reggio Emilia, Italy. Issue 3 (May 2020) - Mancuso, Pamela; Djuric, Olivera; Collini, Giorgia; Serventi, Emanuela; Massari, Marco; Zerbini, Alessandro; Giorgi Rossi, Paolo; Vicentini, Massimo
Abstract : Aims of this population-based cohort study was to compare the overall and site-specific cancer incidence in individuals with alcohol or drug use disorders with incidence of the general population, and to estimate excess cancer risk in a subgroup of individuals who have hepatitis C virus or HIV infection. The study included 4373 residents of Reggio Emilia province diagnosed with alcohol or drug use disorders during the period from 1 January 1985 to 31 December 2014. All newly diagnosed cancers registered from 1 January 1996 to 31 December 2014 were taken into account to calculate the standardised incidence ratio (SIR) of cancers of any site and of site-specific cancers. SIR of cancer at any site was 1.6 (95% confidence interval [CI] 1.4–1.9). Anogenital cancers were associated with the highest excess risk (SIR=11.9; 95% CI 4.9–28.5), followed by oesophageal (SIR=9.5; 95% CI 3.6–25.3) and cervical cancer (SIR=8.6; 95% CI 2.8–26.7). Excess risk of all cancer sites, except for breast cancer, was observed among individuals with alcohol use disorders and of all cancer sites, except breast and kidney cancers, among individuals with drug use disorders. Among hepatitis C virus-positive individuals, cancer at any site risk was 1.9 (95% CI 1.2–3.1) and among HIV-infected individuals it was 3.3 (95% CI 1.8–5.7). Individuals with alcohol and drug use disorders face a higher risk of various cancers. Effective interventions to prevent or reduce the harm of substance abuse and risky behaviours in this population are warranted. Abstract : Supplemental Digital Content is available in the text.